Indications of the past continuous verb in the Holy Quran language study - damir laftat husayn ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
This research focus on studying the continuous aspect in comparison to the perfect aspect in the verb tense, and studies its application to the Qur’anic text. The continuous verb is not studied as a fourth form of the verb (past, present and imperative), but instead it is applied to all of these forms. Each of these forms can be perfect at times, and continuous at other times, depending on the context in which it is mentioned, as the context is what determines the significance of the verb whether it was perfect or continuous. In this research, the past tense was chosen only, in order to indicate the aspect of continuity in it and apply it to examples from the Holy Qur’an to indicate the state of transformation in this verb from the supposed perfection to continuity, as well as showing the possible indications that result from the continuous aspect acquired by the verb due to the context in which it came.